The relation between maternal work hours and cognitive outcomes of young school-aged children - Annemarie Künn-Nelen; Andries de Grip; Didier Fouarge (Institute for the Study of Labor (IZA), 2013)
This paper is the first that analyzes the relation between maternal work hours and the cognitive outcomes of young school-going children. When children attend school, the potential time working mothers miss out with their children, is smaller than when children do not yet attend school. At the same time, working might benefit children through, for example, greater family income. Our study is highly relevant for public policy as in most countries maternal employment rates rise when children enter school. We find no negative relation between maternal working hours and child outcomes as is often found for pre-school aged children. Instead, we find that children's sorting test score is higher when their mothers work part-time (girls) or full-time (boys). Furthermore, we find that planned parent-child activities are positively related to children's language test scores. Nevertheless, we do not find that a richer home environment in terms of the number of parent-child activities provided to the child explain the relation between maternal work hours and children's test scores.
Keywords: D10; J13; J22; 330; intergenerational human capital investments; (non)cognitive skills; maternal labor supply; home environment